Quantification of Reproductive Disorders in Jersey, Hariana and Crossbred Dairy Cattle - SINGH, BALVIR; KUMAR, D; GHOSH, A K (The Indian Journal of Animal Reproduction, 2023)
On the basis of 3484 calving records of 811 Jersey, Hariana and crossbred cows, it was observed that the per cent incidence of reproductive disorders among the progeny of different sires did not fall within the normal range of 30-70%. Susceptibility of prolapse, dystocia, retained placenta, metritis and abnormal bilth was 2.6, 3.0, 3.4, 3.0 and 3.6% in Jersey cows; 4.4, 5.7, 5.8, 5.6 and 6.6% in crossbred and 2.4, 3.1, 3.8, 2.9 and 3.5% in Hariana cows, respectively. Crossbred cattle were more susceptible to these disorders than Hariana and Jersey cattle. These disorders were significantly associated with each other. The skewness and kurtosis were absent for all the disorders in all the genetic groups except for prolapse and abnormal birth in Jersey cattle population.